Metal oxide nanoparticle-modified ITO electrode for high-performance solution-processed perovskite photodetectors. Issue 9 (16th February 2022) - Yan, Chao; Wang, Yue; Zhu, Lijie; Jiang, Jingzan; Hu, Yufeng; Cui, Qiuhong; Lou, Zhidong; Hou, Yanbing; Teng, Feng
Abstract : PPDs based on TiO2 and SnO2 NP layers show similar significantly low dark current density. Due to the UV induced conductivity and barrier height changes in the TiO2 device after UV illumination the dark current of the device increases, while the SnO2 device remains the same. Abstract : Low dark current density plays a key role in determining the overall performance of perovskite photodetectors (PPDs). To achieve this goal, a hole transport layer (HTL) on the ITO side and a hole blocking layer (HBL) on the metal electrode side are commonly introduced in PPDs. Unlike traditional approaches, we realized a high-performance solution-processed broadband PPD using metal oxide (MO) nanoparticles (NPs) as the HBL on the ITO electrode and PC61 BM as another HBL on the metal electrode side to reduce the device dark current. The PPDs based on TiO2 and SnO2 NP-modified layers show similar device performances at −0.5 V: a greater than 10 5 on/off ratio; over 100 dB linear dynamic range (LDR) under different visible light illumination; around 0.2 A W −1 responsivity ( R ); greater than 10 12 jones detectivity ( D *); and ∼20 μs rise time of the device. The MO NP interfacial layer can significantly suppress charge injection in the dark, while the accumulated photogenerated charges at the interface between the MO layer and the perovskite layer introduce band bending, leading to dramatically increased current under illumination. Therefore, the dark current density of the devices is significantly reduced and the optical gain is drastically enhanced. However, after UV illumination, the dark current of the TiO2 device dramatically increases while the dark current of the SnO2 device can stay the same as before since the UV illumination-induced conductivity and barrier height changes in the TiO2 layer cannot recover after removing the UV irradiation. These results indicate that the TiO2 NP layer is suitable for making a vis-NIR photodetector, while the SnO2 NP layer is a good candidate for UV-vis-NIR photodetectors. The facile solution-processed high-performance perovskite photodetector using MO NP-modified ITO is highly compatible with low cost, flexible, and large-area electronics.